ANALISIS AKAD TABUNGAN EMAS DI PEGADAIAN SYARIAH DALAM PERSPEKTIF EKONOMI ISLAM(Studi Kasus Unit Pegadaian Syariah Mlati, Sleman, Yogyakarta) - Aulia Faradita; Abdul Salam; Baiq Ismiati; Febrian Wahyu Wibowo (PT. Hasba Edukasi Mandiri, 2025)
This study aims to analyze the practice of gold savings products at the Mlati Sharia Pawnshop Unit from an Islamic economic perspective and to identify factors that influence customer interest in gold savings products. The background of this study is based on the phenomenon of increasing interest in gold investment because it is considered safe, stable, and profitable, but its implementation still leaves various problems related to contracts, transparency, and customer understanding of sharia principles. This study uses a descriptive qualitative approach method with data collection techniques in the form of interviews, observations, and documentation. Data analysis was carried out with the help of Atlas.ti software version 9. The research sources consisted of unit managers and customers who use gold savings. The results of the study indicate that the Mlati Sharia Pawnshop Unit has succeeded in implementing murabahah and wadi'ah contracts in gold savings appropriately and in accordance with Islamic economic values. However, it is necessary to increase public literacy so that understanding of sharia contracts can be more optimal in supporting the development of the Islamic economy in Indonesia. Customer interest is influenced by several factors, namely, level of understanding, ease of access, economic conditions, perceptions of investment security, and trust in institutions. The conclusion of this study confirms that Pegadaian Syariah has succeeded in presenting affordable, safe, and digital-based financial products, which are in line with the needs of modern society and in accordance with Islamic values. Gold savings at Pegadaian Syariah have great potential to be developed amidst the increasing public interest in sharia-based gold investment.